2003
DOI: 10.1080/0269920031000061786
|View full text |Cite
|
Sign up to set email alerts
|

Exploring aphasic grammar 2: do language testing and conversation tell a similar story?

Abstract: This paper investigates the grammatical difficulties of an English-speaking person with non-fluent aphasia using clinical assessments based on picture description and story telling. The same individual's conversation grammar, which was investigated in detail in a linked article is reviewed here, and the notion that interactional grammatical phenomena may not necessarily be visible in elicited language data is explored. Data analysis shows that the aphasic speaker's grammar looks considerably different in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 11 publications
2
40
0
2
Order By: Relevance
“…However, it is also possible that carryover is not supported because materials and tasks are based on utterances stripped of natural interactional context. Thus, recent research has demonstrated that utterances produced by agrammatic speakers in everyday conversation differ significantly from utterances elicited by assessment and therapy tasks (Beeke, Wilkinson, & Maxim, 2007a, 2003aEdwards, 2000;Kolk & Heeschen, 1992;Wilkinson, 1995). This is because tests target decontextualized language, isolated from an interactional context of real-life talk about needs, opinions, and experiences.…”
Section: Background/literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…However, it is also possible that carryover is not supported because materials and tasks are based on utterances stripped of natural interactional context. Thus, recent research has demonstrated that utterances produced by agrammatic speakers in everyday conversation differ significantly from utterances elicited by assessment and therapy tasks (Beeke, Wilkinson, & Maxim, 2007a, 2003aEdwards, 2000;Kolk & Heeschen, 1992;Wilkinson, 1995). This is because tests target decontextualized language, isolated from an interactional context of real-life talk about needs, opinions, and experiences.…”
Section: Background/literature Reviewmentioning
confidence: 95%
“…It should be noted that we do not necessarily expect to see changes in performance on language tests post therapy; the strategies being taught are contextual, and we already know that utterances elicited by decontextualised tests differ significantly from those produced in conversation (Beeke et al, 2003a(Beeke et al, , 2007aEdwards, 2000). In order to show convincing therapeutic gains, we have begun to develop a quantitative measure of change over time in conversation, as none currently exists.…”
Section: The Conversation Therapy Projectmentioning
confidence: 95%
See 1 more Smart Citation
“…A further benefit of studying conversation is that certain grammatical behaviours that have previously been interpreted as direct symptoms of an underlying linguistic deficit may actually arise from the interactional context in which they are produced (Beeke, Wilkinson, & Maxim, 2003). Grammatical structures allow the listener to anticipate pragmatic, structural, and linguistic sequences.…”
Section: Conversationmentioning
confidence: 99%
“…Experimental data have been interpreted within different theoretical frameworks, for example, generative grammar (e.g., Friedmann & Grodzinsky, 1997;Grodzinsky, 2000;Hagiwara, 1995;Ouhalla 1993), surface descriptive grammar (Edwards 2000;Edwards, Garman, & Knott, 1993), conversational analysis (Beeke, Wilkinson & Maxim, 2003), a psycholinguistic processing framework (Ellis & Young, 1996). A different interpretation of the same phenomena has been proposed by Kolk and Heeschen (Kolk, 1987;Kolk & Heeschen, 1990, who view fluent and non-fluent aphasic speech from a different perspective.…”
mentioning
confidence: 95%